PENGEMBANGAN BUKU AJAR STATISTIK SEBAGAI PENUNJANG PERKULIAHAN - Saidah, Nusrotus (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2016)
This research is a development that aims to develop teaching materials that meet thecriteria and quality. The teaching materials as supporting lectures statistics in order to improvelearning in the classroom so that students have an understanding and skills in statistical skillsindependently. Textbook development procedure consists of four phases: planning, organizing,implementation and evaluation. Textbook material in accordance with the lesson plans thestatistics shown by the example and the same practice with SPSS. Results of the assessment of thereviewer obtained both categories with an average score of 38.41 as seen from all aspects, namely,the aspect of the writing approach, the concept of truth, the depth and breadth of the concept,clarity sentence, linguistic, evaluation, feasibility, structure handouts, physical penampila bookinstructional and reference library. This textbook memeiliki high criteria in truth the concept andstructure of the handout. The development of this textbook in accordance with the syllabus,suitability tests (sample) describing the material, the components of a complete book compiled.Practicability test is done so that the student can pass judgment textbooks with material tailored toability. Practicability test results by the students gain an average score of 92.5 which indicatesvery good or practical to use as a reference source in the course of independent learning statistics